Etiology, diagnosis and treatment of infectious esophagitis - Rosołowski, Mariusz; Kierzkiewicz, Maciej (Gastroenterology Review/Przegląd Gastroenterologiczny, 2013)
Infectious esophagitis may be caused by fungal, viral, bacterial or even parasitic agents. Risk factors include antibiotics and steroids use, chemotherapy and/or radiation therapy, malignancies and immunodeficiency syndromes including acquired immunodeficiency syndrome. Acute onset of symptoms such as dysphagia and odynophagia is typical. It can coexist with heartburn, retrosternal discomfort, nausea and vomiting. Abdominal pain, anorexia, weight loss and even cough are present sometimes. Infectious esophagitis is predominantly caused by Candida species. Other important causes include cytomegalovirus and herpes simplex virus infection.